Answer:
[tex]x+5[/tex]
Step-by-step explanation:
[tex]\left(4x-5\right)-\left(3x-10\right)[/tex]
[tex]\mathrm{Apply\:rule}:\quad \left(a\right)=a[/tex]
[tex]\left(4x-5\right)=4x-5[/tex]
[tex]=4x-5-\left(3x-10\right)[/tex]
[tex]\mathrm{Apply\:the\:distributive\:law}:\quad \:-\left(a-b\right)=-a+b[/tex]
[tex]-\left(3x-10\right)=-3x+10[/tex]
[tex]=4x-5-3x+10[/tex]
[tex]\mathrm{Group\:like\:terms}[/tex]
[tex]=4x-3x-5+10[/tex]
[tex]\mathrm{Add\:the\:numbers:}\:-5+10=5[/tex]
[tex]=4x-3x+5[/tex]
[tex]\mathrm{Add\:similar\:elements:}\:4x-3x=x[/tex]
[tex]=x+5[/tex]